Prevalence and Associated Risk Factors of Hypertension Among Rural Communities in Kudat Sabah, East Malaysia - Syed Shajee, Husain; Mohd Nazri, Mohd Daud; Rhanye, Mac Guad; Wu, Yuan Seng *; Aung, Yin Nwe; Robinson, Fredie; Sasitharrani, A/P Thiruvengadam; Nee, Kee Hooi; Jing, Looi Chun; Naamagal, A/P Rajenthiram; Hani Maisarah, Binti Zahrul Azhar; Han, Ko Jing; et al. (Academy of Sciences Malaysia, 2022)
Approximately a third of Malaysian adult has been diagnosed with hypertension. This study aimed to investigate the prevalence and key risk factors of hypertension in a community living in a rural area of Kudat, Sabah. Methods: The study included participants of at least 18 years old, able to communicate in the local dialect, no mental disability, not pregnant or lactating and no known cause of secondary hypertension. Sociodemographic data were recorded in addition to assessment of depression, anxiety, stress, and dietary salt of the participants using standard DASS-21 questionnaire (Depression Anxiety Stress Scales standard questionnaire) questionnaire. Multiple logistic regression analyses were used to assess the association of hypertension and health-related variables predicted to be a risk factor. Results: Out of 111 participants, 30% were diagnosed with hypertension of which 60.6% were not aware of their health condition. Among the variables analyzed, higher age (at least 40 years old) and excess BMI (≥23.0) highly contributed to the predisposition of hypertension (p<0.05). Other variables such as gender, marital status, education level, physical activity, stress level, and household income were not associated with hypertension (p>0.05). Conclusion: The community in Kudat, as a representation of the rural population in Sabah, has a high prevalence of hypertension, implying that lifestyle changes and regular health checks are effective interventions to minimise the risk of hypertension.